2004
DOI: 10.1074/jbc.m410014200
|View full text |Cite
|
Sign up to set email alerts
|

The Topology of the Lcb1p Subunit of Yeast Serine Palmitoyltransferase

Abstract: The structural organization and topology of the Lcb1p subunit of yeast and mammalian serine palmitoyltransferases (SPT) were investigated. In the yeast protein, three membrane-spanning domains were identified by insertion of glycosylation and factor Xa cleavage sites at various positions. The first domain of the yeast protein, located between residues 50 and 84, was not required for the stability, membrane association, interaction with Lcb2p, or enzymatic activity. Deletion of the comparable domain of the mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 29 publications
3
78
3
Order By: Relevance
“…We have shown that transfection of mammalian cells with the human LCB1 ortholog (SPTLC1) and the LCB2-like isoform, SPTLC2, produces only a modest increase in SPT activity, despite high levels of protein expression (11). The same is true for cotransfection of SPTLC1 and the other LCB2-like isoform, SPTLC3 (9).…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…We have shown that transfection of mammalian cells with the human LCB1 ortholog (SPTLC1) and the LCB2-like isoform, SPTLC2, produces only a modest increase in SPT activity, despite high levels of protein expression (11). The same is true for cotransfection of SPTLC1 and the other LCB2-like isoform, SPTLC3 (9).…”
mentioning
confidence: 55%
“…3B). These results suggest that endogenous levels of ssSPTa limit SPT activity, thus providing an explanation for the lack of a simple correlation between levels of hLCB1 and hLCB2a/hLCB2b expression and SPT activity (11).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The topology of ScORM2 protein was mapped based on the previously described methodology (Han et al, 2004). In brief, NheI restriction sites were created before codons for amino acids 2, 100, 135, and 169 and an XbaI site before the stop codon (217) by use of the QuikChange mutagenesis kit (Agilent Technology).…”
Section: Membrane Topology Mapping Of Scorm2mentioning
confidence: 99%